Powers of the Local Authority in Regulating Land Planning and Development Control: Whither Control - Maidin, Ainul Jaria; Mobarak Ali, Bashiran Begum (MIP, 2009)
Land use planning in Malaysia as regulated by the Town and Country Planning Act 1976 (“Act 172”) vests in the local authorities’ wide powers and responsibility for managing and carrying on the daily administration of land use planning decision making and development control regime. This article examines the powers of the local authority in regulating land planning and development control and the power of the courts in exercising control over the exercise of the discretionary powers of the local authority.